Pengaruh Penambahan Bubuk Jahe Emprit (Zingiber Officinale Var. Amarum) Terhadap Karakteristik Teh Herbal Daun Sirih Merah (Piper Crocatum) - Riska Andini, Dinda; Yusasrini, Ni Luh Ari; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPA, 2023)
Herbal tea is a drink made from ingredients other than the leaves of the plant camellia sinensis. This study aims to determine the effect of adding emprit ginger powder to the characteristics of red betel leaf herbal tea and to determine the appropriate addition of emprit ginger powder to produce red betel leaf herbal tea with the best characteristics. This study used an experimental method with the treatment of gingger powder which consisted of 5 levels, namely: 0%, 10%, 20%, 30%, and 40%. Each treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed using Analysis of Variance (ANOVA) and if the treatment had a significant on the variables, then continued with the Duncan Multiple RangeTest (DMRT). The results showed that the addition of emprit ginger powder had a significant effect on the water content, ash content, tannin content, extract content in water, total phenol, total flavonoids, antioxidant activity, color (hedonic test), aroma (hedonic test and scoring test), taste (hedonic test and scoring test), and overall acceptance (hedonic test). Red betel leaf herbal tea with the best characteristics is the addition of 40% emprit ginger powder with the following characteristics: water content 7.73%, ash content 14.86%, tannin content 1.45 mgTAE/g, extract content in water 72.39%, total phenol 1.45 mgGAE/g, total flavonoids 2.53 mgQE/g, antioxidant activity 75.46%, and had sensory properties with overall acceptance was liked.